Computational Models for the Analysis of positive displacement machines: Real Gas and Dynamic Mesh. (September 2017) - Casari, Nicola; Suman, Alessio; Ziviani, Davide; van den Broek, Martijn; De Paepe, Michel; Pinelli, Michele
Abstract: In recent years, computational fluid dynamics (CFD) has been applied for the design and analysis of positive displacement machines (both compressors and expanders) with numerous challenges due to the dynamics of the compression (or expansion) process and deforming working chambers. The relative motion and in turn, the variation of the gaps during machine operation implies several obstacles for the implementation of reliable CFD models. The majority of the studies reported in literature focused on scroll, twin screw and reciprocating machines. The limitation of the developed methodologies to be applied directly to positive displacement machines with more complex meshing such as that of single-screw has been highlighted in literature. In this paper, a single screw expander is studied by means of (i) a moving mesh technique (dynamic mesh in the Key Frame Remeshing approach) and (ii) a real gas model of a R134a (Peng-Robinson model) implemented in OpenFOAM ®. On the top of that, all the possible techniques that come with the software are investigated in their application to single screw. An useful review of the state of the art CFD with open-source software (OpenFOAM-v1606+ and foam-extend4.0) is therefore carried out. The reliability of CFD model represents indeed the first step on which the design process and further optimization will be based.